PERANCANGAN ALAT PENGAMAN MOTOR DENGAN MEMANFAATKAN SENSOR GETAR DAN GELOMBANG RADIO FM - Ahmad Abtokhi, Burhan, (Jurnal Neutrino, 2009)
Motorcycle is a kind of vehicle that is practical and economical. It is also used as alternative vehicle to avoid the traffic jam. However, nowadays, there are a lot robbing on motorcycle. And this phenomenon makes the user of motorcycle worried. Since the need of security system in motorcycle is increasing, it is crucial to develop the best way of preventing crime on motorcycle. This security system uses trill censor that is connected to transmitter and Capacitor Discharge Ignition (CDI) of motorcycle. This trill censor will detect the change of motorcycle position, send the signal to the receiver tool, and break off the ignition on the motorcycle. This security system uses FM radio wave as the media of its information transmission. Moreover, the trill censor of this system is connected on the series of Bistable Multivibrator as a main controller of  transmitter.  This  series  uses  Astable  Multivibrator,  with  IC  555  as  a  substitute  of  audio transmitter source. The controller of the main series in the transmitter is connected with relay that functions to activate the transmitter and break off the system of ignition on the motorcycle. This Driver Relay uses three transistors C9014 that is used for switching. This driver line is connected with the transmitter and ignition system that is moved by Bistable Multivibrator when it receives the trill. This research finds a tool that is able to detect the movement of motorcycle position from100 metre. And it functions to prevent the motorcycle robbing.Kata Kunci: Sensor, Gelombang Radio, Saklar Transistor, Driver Relay